IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU NOMOR 19 TAHUN 2018 TENTANG PEDOMAN PENGELOLAAN PELAYANAN INFORMASI DAN DOKUMENTASI DI LINGKUNGAN PEMERINTAH KOTA PEKANBARU - Mutiara Mahendra; Zulkarnaini Zulkarnaini (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The Information and Documentation Service Management Policy in the Government of Pekanbaru aims to improve the quality of information and documentation services. Everyone has the right to communicate and obtain public information to develop their personal and social environment, and the right to seek, obtain, possess and store information in order to find out, supervise, and participate in the process of state administration by the government. The purpose of this study is to determine the implementation of information and documentation service management policies and to determine the factors that hinder the implementation of these policies. This research uses purposive sampling technique with qualitative research using a descriptive approach and the required data both primary and secondary data are obtained through observation, interviews, and documentation, for further analysis. This study uses the MSN-Approach theory from Yulianto Kadji. The results of this study indicate that: first, the implementation of information and documentation service management policies within the Pekanbaru city government has not run optimally. Second, the inhibiting factors in implementing the policy are responsibility, facility and outreach